PERCEIVED QUALITY OF TRANSITIONAL CARE BETWEEN PUBLIC HOSPITAL AND PUBLIC HEALTH CARE CLINIC IN NEGERI SEMBILAN, MALAYSIA: A PILOT STUDY - Farhana Md Yusof; Chai-Eng Tan (Malaysian Journal of Public Health Medicine, 2020)
Quality of transitional care affects healthcare spending and service use. Poor transitional care is associated with adverse effects such as medication error and risk of unnecessary readmission. The objective of this study is to evaluate patients’ perception of quality of transitional care from a public tertiary hospital to a public health clinic in Negeri Sembilan. A cross-sectional study was conducted involving 307 respondents from the public health clinic following discharge from the hospital from July to September 2018.Patient’s perception of quality of transitional care was measured using the Care Transitional Measure (CTM 15®) questionnaire. The response rate for this study was 90.6%. The mean CTM-15® score was 73.1 (±13.03) out of a scale of 1 to 100. The mean scores for the various domains were: Critical understanding was 73.3 (±14.33), Preferences important was 71.9 (±14.99), Management preparation was 74.0 (±14.53), and Care plan 73.3 (±14.75). Multiple linear regression showed that age was a significant independent predictor for the CTM-15® scores where elderly patients had poorer scores than young adults (adjusted R2=0.104, p<0.001).In conclusion, the perceived quality of transitional care between the public general hospital and health clinic was good but decreased with patient’s age. This could be due to complexity of the patient’s problems upon discharge.